Diversity management and performance: Evidence from Nigerian multinational companies - Samuel Olufemi Omoyele; Jayeola Olabisi (Economic Review: Journal of Economics and Business, 2020)
This study examines the relationship between diversity management and the performance of Nigerian multinational companies. A single cross-sectional design was adopted for the study and a well-structured questionnaire was administered to 318 randomly chosen senior managers from Mobil Oil, Guinness, Coca-Cola, Nestle, MTN, and Cadbury Plc within Lagos Metropolis. The research instrument was tested for validity and reliability using confirmatory factor analysis and Cronbach's alpha. The independent variable is diversity management while performance (dependent variable) was measured with Employees' Productivity (EP), Profitability Level (PL), and Employees' Innovativeness (EINV). The data collected were analyzed using Correlation Analysis and Structural Equation Modelling (SEM) factor to determine the relationship between diversity management and performance of Nigerian Multinational Companies. The results revealed a significant and positive relationship between diversity management and the performance of Nigerian multinational companies. The study concluded that diversity management motivates employees to put in their best to achieve a high level of productivity which leads to improved profitability due to employees' innovativeness. Therefore, the study suggests that multinational companies in Lagos Metropolis should ensure proper management of diversity in the workplace.
Keywords: M14; M52; M150; 330; diversity; productivity; profitability; innovativeness